From Graduation to Employment: Tracking the Career Paths of BSEd Physical Science Alumni at Isabela State University - Jonathan Lord R. Aquino (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study explored the career trajectories and employability of 41 Bachelor of Secondary Education (BSEd) Physical Science graduates from Isabela State University-Cauayan Campus, focusing on those who completed their studies between 2017 and 2019. Using a descriptive survey approach, data were gathered from 41 graduates through a structured questionnaire. The results indicate that most graduates were young, single women from rural, low-income backgrounds in Isabela. Despite these socioeconomic hurdles, a notable 78.04% successfully entered the teaching field by passing the licensure exam. Graduates reported high satisfaction with the knowledge and skills gained from the program, especially in areas such as accommodating diverse learners and engaging in reflective teaching practices. However, there is a need to enhance basic skills such as literacy, communication, and critical thinking. The choice of educational institution and program was largely influenced by cost-effectiveness and employment opportunities in the field. Employment statistics show that while most graduates found jobs related to their degrees, challenges remained concerning job security, income, and alignment with career aspirations. Only a small fraction pursued further education for career progression purposes. This study underscores the necessity for ongoing curriculum development, enhanced career support services, targeted socioeconomic programs, and regular alumni feedback to boost graduate readiness and adaptability in the changing job market. These findings provide valuable insights for educational stakeholders to align programs with community needs and broader industry trends, thereby improving the success of BSEd Physical Science graduates in teaching and related fields.